A Distinct EEG Marker of Celiac Disease‐Related Cortical Myoclonus. Issue 4 (30th November 2020) - Swinkin, Emily; Lizárraga, Karlo J.; Algarni, Musleh; Garcia Dominguez, Luis; Baarbé, Julianne K.; Saravanamuttu, James; Chen, Robert; Slow, Elizabeth; Lang, Anthony E.; Wennberg, Richard A.
ABSTRACT: Background: Celiac disease is associated with motor cortex hyperexcitability and neurological manifestations including cortical myoclonus. Electroencephalography abnormalities have been described, but no distinct pattern has been reported. Methods: We describe the neurophysiological characteristics of 3 patients with celiac‐associated cortical myoclonus using electroencephalography, magnetoencephalography, and transcranial magnetic stimulation. Results: Electroencephalography in all cases demonstrated lateralized low‐amplitude, electropositive beta‐frequency polyspike activity over the central head region, corresponding to motor cortex contralateral to the myoclonic limb. Jerk‐locked back‐averaging demonstrated a preceding cortical potential; magnetoencephalography source localization revealed a cortical generator in the posterior wall of the precentral gyrus for the back‐averaged potential and oscillatory abnormality. In 1 patient, cerebellar inhibition of the motor cortex was physiologically normal. Conclusions: Central head oscillatory, low‐amplitude, electropositive electroencephalography polyspike activity may be a distinct marker of celiac‐related cortical myoclonus and is consistent with celiac‐related motor cortex hyperexcitability, which may not necessarily result from cerebellar disinhibition. © 2020 International Parkinson and Movement Disorder Society